Preparation of Papers for IFAC Conferences & Symposia: Adaptive fixture system for reducing machining distortion caused by residual stresses in milling. Issue 2 (2022) - Landwehr, M.; Kalocsay, R.; Kolvenbach, C.; Ganser, P.; Bergs, T.
Abstract: Machining distortion caused by residual stresses is one of the major challenges in the production of thin-walled monolithic parts, which are widely used in the aerospace industry. The relevant influencing factors include the selected process parameters, the machining sequence as well as the used fixture system. This paper presents an adaptive fixture system for reducing machining distortion caused by residual stresses in milling. To validate the advantage of this system, machining distortion experiments are conducted on monolithic parts made of Ti-6A1-4V using a conventional and the adaptive fixture system.